Sistem Informasi Persediaan Barang Operasional Hotel Berbasis Web - Aldo, Dasril; Nengsih, Yeyi Gusla; Wijaya, Trisno (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Lovina Inn Hotel is a hotel that provides services to tourism guests in Batam City. At this time, in storing inventory data, it still uses a record book, so that when searching for inventory information, incoming and outgoing goods are still carried out in a recording form. The purpose of this study is to design an information system for operational goods inventory at the Lovina Inn hotel so that it makes it easier to manage data by not doing manual recording. With the application of a structured analysis model method for the creation of an Operational Inventory Information System, it can make it easier to build a system using the PHP language (Hypertext Preprocessor) and a database using MySQL. This application is designed to make it easier for the hotel to manage the incoming and outgoing stock of goods to the hotel operational inventory report